2021
DOI: 10.3389/fgene.2021.615834
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Six-Gene-Based Prognostic Model Predicts Survival and Clinical Risk Score for Gastric Cancer

Abstract: Background: Autophagy plays a vital role in cancer initiation, malignant progression, and resistance to treatment. However, autophagy-related genes (ARGs) have rarely been analyzed in gastric cancer (GC). The purpose of this study was to analyze ARGs in GC using bioinformatic analysis and to identify new biomarkers for predicting the overall survival (OS) of patients with GC.Methods: The gene expression profiles and clinical data of patients with GC were obtained from The Cancer Genome Atlas (TCGA) and Gene Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…Izumi et al 29 constructed a gene expression-based 15-gene signature to distinguish lymph node status and obtained an AUC value of only 0.829 in the GSE62254 cohort. Li et al 30 constructed a six gene-based prognostic model in the TCGA-STAD cohort; however, the AUC value they validated in GSE62254 was only 0.60-0.63. In addition, the prognostic model we established was an independent prognostic factor after adjusting for the clinical features of age, sex, stage, grade, and EBV status.…”
mentioning
confidence: 99%
“…Izumi et al 29 constructed a gene expression-based 15-gene signature to distinguish lymph node status and obtained an AUC value of only 0.829 in the GSE62254 cohort. Li et al 30 constructed a six gene-based prognostic model in the TCGA-STAD cohort; however, the AUC value they validated in GSE62254 was only 0.60-0.63. In addition, the prognostic model we established was an independent prognostic factor after adjusting for the clinical features of age, sex, stage, grade, and EBV status.…”
mentioning
confidence: 99%
“…In order to investigate the research status of PLOD2 and gastric cancer, we conducted a search on the PubMed using the following search strategy: [“stomach neoplasms” (Title/Abstract) OR “stomach neoplasms” (MeSH Terms) OR “gastric adenocarcinoma” (Title/Abstract)] AND [“PLOD2” (Title/Abstract)]. Finally, seven studies were found ( Kiyozumi et al, 2018 ; Li S. S et al, 2020 ; Luo et al, 2020 ; Wang et al, 2020 ; Dai et al, 2021 ; Li et al, 2021 ; Song et al, 2021 ). Dai et al constructed a prognostic model for five genes including PLOD2 , which was subsequently validated by RT-PCR in normal tissue and gastric cancer cell lines ( Dai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, their study did not perform analyses related to tumor immunity (including infiltrating immune cells, TMB, etc.). Similarly, Li J et al( Li et al, 2021 ), Li SS et al ( Li S. S et al, 2020 ), Luo et al ( Luo et al, 2020 ), and Song et al( Song et al, 2021 ) were also constructed multiple genes (including PLOD2 ) prognostic model, but all lacked tumor immune-related analysis or only had comparisons of different immune cell classifications. Kiyozumi et al study showed that PLOD2 promotes cell invasion and migration in gastric cancer under hypoxic conditions and leads to dissemination to the peritoneum, in vitro ( Kiyozumi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are far from exhaustive and may be further explored in terms of the long noncoding genes and alternative splicing expression patterns. For instance, DYNLL1 alternative splicing expression, which is significantly decreased in EGCG+HC treated glioma cells, is reported to be upregulated in gastric cancer high-risk group patients and hepatocellular cancer ( Berkel and Cacan, 2020 ) ( Li et al, 2021 ). How DYNLL1 promotes aberrant transcription in cancers are still unknown.…”
Section: Discussionmentioning
confidence: 99%